Pengaruh Kualitas Pelayanan, Kualitas Produk, Dan Harga Terhadap Loyalitas Pelanggan “Ada Swalayan” Siliwangi Semarang Melalui Kepuasan Konsumen Sebagai Variabel Intervening - Bachtiar, Dava Tri Agutama; Anomsari, Ariati; Chasanah, Amalia Nur; Farida, Ida (Politeknik Negeri Ambon, 2024)
This research uses a quantitative explanatory survey approach, by distributing questionnaires as a data collection technique. The sampling method used in this research is purposive sampling using the Cochran formula for sampling because the population size is too large and unknown. The research sample consisted of 100 respondents who were consumers of